Helobdella buzz n. sp. (Clitellata: Hirudinida), a bromeliad leech from the Brazilian Atlantic Forest - Iwama, Rafael Eiji; Nogueira, João Miguel De Matos; Gonçalves, Ana Zangirolame (Zootaxa, 2017)
Tank bromeliads are important components of tropical forests and are capable of hosting many species of invertebrates in their tank water, such as insect larvae, ostracods and oligochaetes (Frank & Lounibos 2009; Jocque & Field 2014; Richardson 1999).